"SHAKTI": A Strategic Marketing Approach of FMCG Giant, HUL-Enabling a Journey towards Business Excellence in the Era of Globalization - Majumder, Indrani (Indian Journal of Marketing, 2009)
Business Excellence can not be attributed to a common set of actions and it doesn’t happen overnight. A ’Strategic Approach’ is the urgency which requires renewed conceptual understanding and significant insights into the contemporary environment. This makes the transformation of tactical marketing activities into strategic marketing essential. Today cost-efficiency does not provide long-term competitive advantage for companies whereas marketing, when conducted strategically, does (Kotler, 1999). In this study an attempt has been made for understanding of the strategic background of the project ’SHAKTI’, a rural marketing initiatives of FMCG giant HUL, which the organization is thinking as the only option for sustenance and for excellence, in the era of globalization.